2019
DOI: 10.48550/arxiv.1907.04741
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Matroid Bases with Cardinality Constraints on the Intersection

Abstract: Given two matroids M 1 = (E, B 1 ) and M 2 = (E, B 2 ) on a common ground set E with base sets B 1 and B 2 , some integer k ∈ N, and two cost functions c 1 , c 2 : E → R, we consider the optimization problem to find a basis X ∈ B 1 and a basis Y ∈ B 2 minimizing cost e∈X c 1 (e)+ e∈Y c 2 (e) subject to either a lower bound constraint |X ∩Y | ≤ k, an upper bound constraint |X ∩ Y | ≥ k, or an equality constraint |X ∩ Y | = k on the size of the intersection of the two bases X and Y . The problem with lower bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Hradovic, Kasperski & Zieliński [11,10] obtain a polynomial time algorithm for the recoverable matroid basis problem and a strongly polynomial time algorithm for the recoverable spanning tree problem. These results have been generalized and improved by Lendl, Peis & Timmermans [15] who show that the recoverable matroid basis and the recoverable polymatroid basis problem can both be solved in strongly polynomial time. Iwamasa & Takayawa [12] further generalize these results and cover cases with nonlinear and convex cost functions.…”
Section: Introductionmentioning
confidence: 87%
“…Hradovic, Kasperski & Zieliński [11,10] obtain a polynomial time algorithm for the recoverable matroid basis problem and a strongly polynomial time algorithm for the recoverable spanning tree problem. These results have been generalized and improved by Lendl, Peis & Timmermans [15] who show that the recoverable matroid basis and the recoverable polymatroid basis problem can both be solved in strongly polynomial time. Iwamasa & Takayawa [12] further generalize these results and cover cases with nonlinear and convex cost functions.…”
Section: Introductionmentioning
confidence: 87%
“…This is a special case of the recoveralbe robust matroid basis problem with interval uncertainty studied in [LPT19], where a strongly polynomial time algorithm for this problem is given. Our problem corresponds to the special case of partition matroids, hence, we arrive at the following observation.…”
Section: (Strategy Ii)mentioning
confidence: 99%
“…The motivation of these problems comes from the recoverable robust matroid basis problem [2]. Lendl et al [17] showed that the problems (1)-( 3) are polynomial-time solvable: they developed a new primal-dual algorithm for the problem (1); and reduced the problems ( 2) and (3) to weighted matroid intersection. By this result, they affirmatively settled an open question on the strongly polynomial-time solvability of the recoverable robust matroid basis problem under interval uncertainty representation [11,12].…”
Section: Minimizementioning
confidence: 99%
“…Lendl et al [17] further discussed two kinds of generalizations of the above problems. One is a polymatroidal generalization.…”
Section: Minimizementioning
confidence: 99%
See 1 more Smart Citation